4′-Chlorobiphenyl-4-yl 2,2,2-trichloroethyl sulfate - Hans-Joachim Lehmler; Larry W. Robertson; Sean Parkin; Xueshu Li (Acta Crystallographica Section E, 2008)
The title compound, C14H10Cl4O4S, is an intermediate in the synthesis of the PCB sulfate monoester of 4′-chloro-biphenyl-4-ol. Both the sulfate monoester and 4′-chloro-biphenyl-4-ol are metabolites of PCB 3 (4-chlorobiphenyl). There are two molecules with different conformations in the asymmetric unit. The solid state dihedral angles between the benzene rings are 18.52 (10) and 41.84 (16)° in the two molecules, whereas the dihedral angles between the least-squares plane of the sulfated benzene ring and O—S (Ar—C—O—S) are 66.2 (3) and 89.3 (3)°. The crystal was an inversion twin with a refined component fraction of 0.44 (7).